2018
DOI: 10.1042/bsr20170681
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of long non-coding RNA SNHG20 promotes ovarian cancer progression via Wnt/β-catenin signaling

Abstract: Long non-coding RNA small nucleolar RNA host gene 20 (SNHG20) has been demonstrated to play crucial regulatory roles in many types of cancer. However, the biological function of long ncRNA (lncRNA) SNHG20 in ovarian cancer is still unclear. In the present study, we found that lncRNA SNHG20 was significantly increased in ovarian cancer. In addition, lncRNA SNHG20 knockdown suppressed the ovarian cancer progression, whereas overexpression of SNHG20 showed the opposite effects. Moreover, our results also revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…Besides, high‐expression of SNHG20 was observed in human gastric cancer cell lines . Similar results about the high‐expression status of SNHG20 expression were found in female common cancers including cervical cancer , ovarian cancer and breast cancer . The expression of SNHG20 in osteosarcoma was still unknown.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Besides, high‐expression of SNHG20 was observed in human gastric cancer cell lines . Similar results about the high‐expression status of SNHG20 expression were found in female common cancers including cervical cancer , ovarian cancer and breast cancer . The expression of SNHG20 in osteosarcoma was still unknown.…”
Section: Discussionmentioning
confidence: 59%
“…Besides, Li et al revealed silencing of SNHG20 inhibited cell proliferation, invasion, and migration, and cell cycle progression in colorectal cancer . The oncogenic function of SNHG20 was also observed in gastric cancer , cervical cancer , ovarian cancer , and breast cancer .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The small nucleolar RNA host gene 20 (SNHG20) lncRNA is located on 17q25.2 and contains 2,183 nucleotides. Several studies have reported that SNHG20 is involved in promoting several common types of human cancer, including hepatocellular carcinoma (Hcc) (14,15), non-small cell lung cancer (NScLc) (16), colorectal cancer (17), ovarian cancer (18), gastric cancer (19) and breast cancer (20). For example, SNHG20 was found to be significantly upregulated in HCC and colorectal cancer, and the high expression of SNHG20 was a predictor of poor prognosis (15,17).…”
Section: Introductionmentioning
confidence: 99%
“…Wnt/β-catenin signal pathway has been revealed to be involved in the regulation of cell proliferation, migration, and invasion in certain cancers [29,30]. It was reported that lncRNA SNHG20 could promote the proliferation, migration, and invasion of bladder cancer and ovarian cancer by activating the Wnt/β-catenin signal pathway [27,31]. Moreover, several important pathway was confirmed to be modulated by SNHG20 in various cancers, including GSK-3β/β-catenin signaling pathway in gastric cancer [28], MDM2-p53 pathway and PTEN/PI3K/AKT signaling pathway in glioma [32,33], PI3K/Akt/mTOR signaling pathway in glioblastoma [17], ATM-JAK-PD-L1 pathway in ESCC [25], and MEK/ERK pathway in cervical cancer [34].…”
Section: Discussionmentioning
confidence: 99%